2004
DOI: 10.1002/cne.20369
|View full text |Cite
|
Sign up to set email alerts
|

Organization of hypocretin/orexin efferents to locus coeruleus and basal forebrain arousal‐related structures

Abstract: Hypocretin/orexin neurons give rise to an extensive projection system, portions of which innervate multiple regions associated with the regulation of behavioral state. These regions include the locus coeruleus, medial septal area, medial preoptic area, and substantia innominata. Evidence indicates that hypocretin modulates behavioral state via actions within each of these terminal fields. To understand better the circuitry underlying hypocretin-dependent modulation of behavioral state, the present study charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(99 citation statements)
references
References 57 publications
(76 reference statements)
6
93
0
Order By: Relevance
“…Published reports from tracing, ultrastructural and chemoarchitectonic studies have shown that the small OX neuronal population emits numerous projections throughout the neuraxis from the olfactory bulb and cerebral cortex to the spinal cord (Broberger et al 1998;Elias et al 1998;Cutler et al 1999;Date et al 1999Date et al , 2000Horvath et al 1999;Nambu et al 1999;Bayer et al 2001;Baldo et al 2003;Caillol et al 2003;Guan et al 2003;Sakamoto et al 2004;España et al 2005;Fadel et al 2005;Kirouac et al 2005;Lee et al 2005;Stoyanova and Lazarov 2005;Balcita-Pedicino and Sesack 2007;Oldfield et al 2007;Shibata et al 2008;Shin et al 2008). These findings were corroborated by evaluations of development (Steininger et al 2004;Steininger and Kilduff 2005) neurophysiological investigations (Bayer et al 2002(Bayer et al , 2004Fadel and Deutch 2002;Martin et al 2002;Zheng et al 2005;Bisetti et al, 2006) and comparative approaches (Iqbal et al 2001;McGranaghan and Piggins 2001;Mintz et al 2001;Moore et al 2001;Novak and Albers 2002;Horowitz et al 2005;Takakusaki et al 2005;S...…”
Section: Introductionsupporting
confidence: 72%
“…Published reports from tracing, ultrastructural and chemoarchitectonic studies have shown that the small OX neuronal population emits numerous projections throughout the neuraxis from the olfactory bulb and cerebral cortex to the spinal cord (Broberger et al 1998;Elias et al 1998;Cutler et al 1999;Date et al 1999Date et al , 2000Horvath et al 1999;Nambu et al 1999;Bayer et al 2001;Baldo et al 2003;Caillol et al 2003;Guan et al 2003;Sakamoto et al 2004;España et al 2005;Fadel et al 2005;Kirouac et al 2005;Lee et al 2005;Stoyanova and Lazarov 2005;Balcita-Pedicino and Sesack 2007;Oldfield et al 2007;Shibata et al 2008;Shin et al 2008). These findings were corroborated by evaluations of development (Steininger et al 2004;Steininger and Kilduff 2005) neurophysiological investigations (Bayer et al 2002(Bayer et al , 2004Fadel and Deutch 2002;Martin et al 2002;Zheng et al 2005;Bisetti et al, 2006) and comparative approaches (Iqbal et al 2001;McGranaghan and Piggins 2001;Mintz et al 2001;Moore et al 2001;Novak and Albers 2002;Horowitz et al 2005;Takakusaki et al 2005;S...…”
Section: Introductionsupporting
confidence: 72%
“…For example, we found that ipsilateral or contralateral inhibition of LC neurons did not block the effects of unilateral Hcrt stimulation. This may be due to the fact that efferent projections from Hcrt neurons typically project both ipsilaterally and contralaterally to downstream brain regions (39). Therefore, inhibiting the LC only on the ipsilateral or the contralateral side would still allow Hcrt neurons to excite the noninhibited LC.…”
Section: Discussionmentioning
confidence: 99%
“…Reward and arousal related efferent projections from LH include VTA [60], PFC [93], lateral habenula and locus coeruleus (LC) [94]. LH also sends projections to the midline thalamus including the paraventricular thalamus (PVT) [95,96].…”
Section: Lh Efferent Projectionsmentioning
confidence: 99%